Comparative Analysis of Loads from the Travelling Cranes of Different Producers - Pichugin, Sergiy; Patenko, Iuliia; Maslova, Svitlana (International Journal of Engineering and Technology, 2018)
The comparative analysis of travelling cranes of national and foreign producers is given in the paper. The travelling cranes of concern Demag were taken into consideration among the foreign cranes. The operation conditions of cranes were analyzed according to different codes of practice. The geometrical parameters, load and weight characteristics of overhead cranes were also compared. For the calculation the horizontal and vertical loads of cranes the most unfavorable schemes of location of bridge cranes on the structures of a production building were defined. According to these schemes, the maximum loads on the frame of the building were calculated and the maximum efforts in the crane beams were determined. Using obtained internal efforts the cross sections of crane girders with a span of 6 and12 mwere calculated. The results of the comparison showed the advantages of the modern cranes in materials saving of steel structures of industrial buildings.Â Â